A Criterion for Effective Complete Decomposability of Abelian Groups - Khisamiev, Nazif; Roman'kov, Vitalii; Tynybekova, Saule (Eurasian Mathematical Journal, 2022)
The notion of effective 〈p, ω〉-decomposability of an abelian group is introduced and a criterion for such decomposability is obtained.